The Evaluation of “Merdeka Belajar-Kampus Merdeka” Program: A Breakthrough or a Wrong Way - Neneng Susanti; Rahmat Salam; Rr Dyah Eko Setyowati; Bintang R Simbolon; Tekat Sukomardojo; Syukra Alhamda; Fakhry Amin; Dwi Prasetyo (AL-ISHLAH: Jurnal Pendidikan, 2023)
The Merdeka Belajar-Kampus Merdeka (hereinafter, MBKM) or independence campus provides opportunities for students and lecturers to strengthen student-based learning programs. This program also supports students’ soft skills in their learning process. This paper aims to evaluate the implementation of this program in teaching and learning activities to improve the quality of education in private universities in Indonesia. This research was conducted using a quantitative approach. Data collection was carried out by distributing questionnaires through an online survey. Descriptive statistical analysis was used to analyze the data. The results show that for students who have participated in the MBKM program, it provides benefits such as providing additional competence in solving problems, improving soft skills, competence for job opportunities, and competence for post-college preparation. As for the lecturers themselves, they will increase their capacity by internalizing the MKBM program and previous programs before the MKBM, concentrating on preparing for the implementation of the MKBM program, having experience in conducting MKBM program guidance for students, and having expertise in designing learning goals (CPL) and credits’ conversion.